Book 12 - Mallery, Susan (Don Mills, Ont., 2013)
Isabel Beebe thinks shes cursed in the romance department. Her teenage crush, Ford Hendrix, ignored all her letters. Her husband left her for another man. So Isabel has come home to dust off her passion for fashion and run the family bridal shop until her parents are ready to sell it. Then she will pursue her real dreams. At least thats the plan until sexy, charming Ford returns and leaves her feeling fourteen all over again. Seeing Isabel all grown up hits bodyguard trainer Ford like a sucker punch. Back when heartbreak made him join the military, her sweet letters kept him sane. Now he cant take his eyes or his lips off her. The man who gave up on love has a reason to stay in Fools Gold forever if three little words can convince Isabel to do the same.
Keywords: Man-woman relationships; Fiction; Divorced women; Fiction; Romance